1992
DOI: 10.1038/355273a0
|View full text |Cite
|
Sign up to set email alerts
|

MutT protein specifically hydrolyses a potent mutagenic substrate for DNA synthesis

Abstract: Errors in the replication of DNA are a major source of spontaneous mutations, and a number of cellular functions are involved in correction of these errors to keep the frequency of spontaneous mutations very low. We report here a novel mechanism which prevents replicational errors by degrading a potent mutagenic substrate for DNA synthesis. This error-avoiding process is catalysed by a protein encoded by the mutT gene of Escherichia coli, mutations of which increase the occurrence of A.T----C.G transversions 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
678
1
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 865 publications
(709 citation statements)
references
References 15 publications
24
678
1
6
Order By: Relevance
“…coli cells contain three MutT-type proteins (MutT, Orf135, and Orf17) that catalyze the hydrolysis of 8-OH-dGTP in vitro [13][14][15]. When 8-OH-dGTP was introduced into E. coli strains lacking MutT or Orf135, and a strain expressing the antisense RNA for Orf17, a phenotype was observed only for mutT cells [18,19,42].…”
Section: In Addition Rai Et Al Recently Reported That the Suppressimentioning
confidence: 99%
“…coli cells contain three MutT-type proteins (MutT, Orf135, and Orf17) that catalyze the hydrolysis of 8-OH-dGTP in vitro [13][14][15]. When 8-OH-dGTP was introduced into E. coli strains lacking MutT or Orf135, and a strain expressing the antisense RNA for Orf17, a phenotype was observed only for mutT cells [18,19,42].…”
Section: In Addition Rai Et Al Recently Reported That the Suppressimentioning
confidence: 99%
“…DNA polymerases incorporate 8-OH-dGTP opposite C and A in vitro [7,[16][17][18][19][20][21][22][23]. In terms of the accumulation of 8-OH-Gua in DNA, the contribution of 8-OH-dGTP from the nucleotide pool and the direct oxidation of G bases in DNA has been reported to be almost equal [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nunoshiba et al reported that the mutations found in an Escherichia coli strain lacking superoxide dismutases and a repressor for iron-uptake systems were A:TC:G and G:CT:A transversions, and concluded that the former was caused by 8-OH-dGTP, based on a variety of experimental data [25]. The E. coli MutT protein catalyzes the hydrolysis of 8-OH-dGTP [16], and A:TC:G transversions are induced with high frequency in mutT mutant strains [24,26,27], indicating the importance of 8-OH-dGTP as a source of mutations. Moreover, the presence of mammalian homologues of MutT (MTH1 proteins) supports this speculation [28].…”
Section: Introductionmentioning
confidence: 99%
“…The damaged DNA precursors formed in the nucleotide pool would be hydrolyzed to the corresponding monophosphates by nucleotide pool sanitization enzymes before they are incorporated into DNA. E. coli MutT and its functional homologues in yeast Saccharomyces cerevisiae (YLR151c) and mammalian cells (MTH1) hydrolyze 8-OH-dGTP [10][11][12]. Nucleotide pool sanitization activities have been identified for two E. coli proteins, Orf135 and Orf17 [13,14].…”
Section: Introductionmentioning
confidence: 99%